Analisis Clustering Dokumen Tugas Akhir Mahasiswa Sistem Informasi Universitas Nasional menggunakan Metode K-Means Clustering - Genius Zendrato, Frankly Sept; Triayudi, Agung; E, Endah Tri (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The purpose of this study was to determine the results of the analysis of the final project document for students majoring in information systems, National University. The research data is grouped based on the theme, object and research method. In this study, the K-Means Clustering method will be used which in the data includes the type of final project, year of publication and reasons for selecting the data. The data collection technique was chosen from the thesis document. The subjects in this study were part of the document that was processed in the abstract. Based on the results of the Clustering process above using the K-means algorithm method and the rapidminer application, it is concluded; 1) In the three clusters, it shows that the final project data 1 has 3 data, the final project 2 has 5 data, the final project 3 has 3 data and the final project 4 has 5 data., 2) In the three clusters the data is the most years old. group 3, namely in cluster 2 there are 3 data, cluster 3 there is 1 data, 3) In the three clusters, it shows that the data for the selection of 3 at least in cluster 2 there is 1 data.